Pollution from cooking in rural and poor urban households of Africa: A methodological review - Gangiah, Sasi (AOSIS, 2022)
The article examines the effect of cooking food in kitchens on the health of women, as women and children are at a greater risk to indoor air pollution (IAP). It is important to study the cooking practices and prevalent behaviours among African women to understand the magnitude of the danger they face. The study suggests that a decline in the combustion of solid fuels and the use of clean energy can improve health among women and children, as well as sustainability goals. Proverbs 17:22 says, ‘A joyful heart is the health of the body, but a depressed spirit dries up the bones’. Bible verse Numbers 35:33–34 indicates, ‘You shall not pollute the land in which you live’. The cooking fuel analysis framework among rural women in Africa will guide forward the governments’ sustainability policies for communities to ensure healthy lives and promote well-being of women and children. Contribution: The article conducts a comprehensive analysis of the literature on African cooking practices. A combined search string is made with keywords. Thematic content analysis is conducted with NVivo (produced by QSR International). The article covers two themes, namely improved well-being and suggesting policies to combat climate change and its impacts. Policies and schemes at grassroots levels and better economic conditions in African countries can help to overcome challenges and change health-damaging cooking behaviours. The new advanced sustainability analysis framework has the potential to influence modern kitchen fuels and increase the adoption of new technologies in African villages.
Keywords: cooking; rural women; biomass; iap; health issues; sustainability goals; policies